"Eles não entenderam o que leram: trajetos de memória na interpretação de obras ficcionais no audiovisual - Yamada, Raul Yudi Mendes (Universidade Federal de São Carlos, 2024)
This Monograph aims to analyze the assertion: "The people complaining didn"t read Sandman or didn"t understand what they read," made by Neil Gaiman during an interview with the Omelete website in response to racist and misogynistic remarks by some fans. In this monograph, we partially disagree with this statement, demonstrating that the memory of other viewed works and the collective memory acquired through social interaction allows for interpretations different from those intended by the authors and directors of the work, leading to statements like those uttered by these fans. Thus, to examine the effect of memory on the understanding of a work, we chose to analyze two audiovisual works: Starship Troopers (1997) and The Boys (2019). The theoretical foundation draws upon the studies of Collective Memory by Maurice Halbwachs (2002 [1925]; 1990 [1950]) and Discursive Memory by Jean-Jacques Courtine (2006; 2009). The work concludes by stating that there is a dynamic discourse directly influencing the expected understanding of the work by the author, and this discourse is related to the crisis of Western masculinity and the quest to reclaim "masculinist values"
They didn't understand what they read": memory in the interpretation of ficcional works in the audiovisual
Keywords: Memória coletiva; Interpretação; História do cinema; LINGUISTICA, LETRAS E ARTES::ARTES